Safety Evaluation of Certain Food Additives : Sixty-eighth Meeting of the Joint FAO/WHO Expert Committee on Food Additives. (WHO Food Additives., 2008)
This volume contains monographs prepared at the sixty-eighth meeting of the Joint FAO/WHO Expert Committee on Food Additives (JECFA) which met in Geneva Switzerland from 19 to 28 June 2007. The toxicological monographs in this volume summarize the safety data on a number of food additives: acidified sodium chlorite asparaginase from Aspergillus oryzae expressed in Aspergillus oryzae carrageenan and processed Euchema seaweed cyclotetraglucose and cyclotetraglucose syrup isoamylase from Pseudomonas amyloderamosa magnesium sulfate phospholipase A1 from Fusarium venenatum expressed in Aspergillus.